2014
DOI: 10.1016/j.proeng.2014.12.440
|View full text |Cite
|
Sign up to set email alerts
|

Application of Taguchi Method for Determining Optimum Surface Roughness in Wire Electric Discharge Machining of P/M Cold Worked Tool Steel (Vanadis-4E)

Abstract: This paper introduced on advancing the wire electrical discharge machine (WEDM) process parameters for the normal surface roughness (Ra) acquired in machining of VANADIS 4e (Powder metallurgical cold worked Tool steel). The Machining analyses were performed at WEDM machine utilizing 0.25 mm wire as electrode material on p/m cold worked tool steel. Taguchi L 27 orthogonal array (OA) was utilized to outline of trial. Ideal methodology parameters were resolved utilizing the signal-to-noice (S/N) proportion which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“…Wire EDM [190]. This grade has very good ductility, high abrasive/adhesive wear resistance, and high compressive strength.…”
Section: Vanadis-4ementioning
confidence: 99%
See 1 more Smart Citation
“…Wire EDM [190]. This grade has very good ductility, high abrasive/adhesive wear resistance, and high compressive strength.…”
Section: Vanadis-4ementioning
confidence: 99%
“…The effect of process parameters on the performance parameters was also analyzed using the Taguchi method. For example, in one study [190], the effect of wire EDM process parameters was investigated for normal SR during the machining of powder metallurgical cold-worked tool steel, VANADIS 4e. The study utilized the Taguchi method to determine the optimum SR.…”
Section: Performance Measures In Edm Of Tool Steelsmentioning
confidence: 99%
“…Ugrasen et al [16] used Taguchi method close to the extortion neural framework to refresh the precision, surface seriousness and MRR. They found that for the more than three responses, current is the most goliath factor Sudhakara and Prasanthi [17] investigated machining parameters for tool steel in WEDM. They found the range perfect setting of different parameters as pulse on time = 108-128 μsec, beat off time = 47-63 μsec, peak stream = 11-13 Amperes, begin opening set voltage = 18-68 Volts, wire strain = 2-8 Grams and water weight = 8-14 Kg/cm 2 .…”
Section: Literature Surveymentioning
confidence: 99%
“…LITERATURE REVIEW-D.Sudhakara et al introduced the promotion of the wire cut EDM machining factors for the roughness of the surface, 0.25mm diameter wire is used for machining the material named as VANADIS 4e, L27 orthogonal array was designed by the Taguchi method for performing experiments, S/N ratio was applied for finding out the rank of each parameter on surface roughness and ANOVA was used for finding the percentage involvement of each factors on response [3]. S V Subrahmanyam et al investigated to optimize the effects of eight input process parameters on Surface Finish during the machining of EN-31 using Taguchi L36 orthogonal array and with the help of ANOVA, S/N ratio and Math model the optimal input parameter combination for the Surface Finish on the WEDM machined arrived and said that it will be useful for the people who do not have much idea of WEDM [4].…”
Section: Introductionmentioning
confidence: 99%